Factors Influencing Psychological Well-being Among Postgraduate Students In Malaysian Research Universities - Ooi, Hui Xian (2023)
In postgraduate education, students were exposed to a wider range of challenging scenarios that forced them outside of their comfort zones and affected their psychological well-being. The study aimed to investigate the predictors of postgraduate students’ psychological well-being (PWB) in Malaysian research universities (MRU). In addition, the second aim of this study was to examine whether gender has moderating effects on the relationship between personality traits (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) and postgraduate students’ PWB. In the present study, the population was postgraduate students in MRU. The total sample size was 297 respondents. This study used the quantitative method to answer the research questions. The sample was selected using purposive sampling. An online questionnaire link (Google Form) was distributed via postgraduate student groups. External factors (supervision, social support, and university support) and internal factors (academic writing skills, self-esteem, self-regulated learning, and personality traits-neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) functioned as the predictors, and PWB as the dependent variables. The items questionnaire was adapted based on the instrument namely Postgraduate Research Experience Survey (PRES) 2007, The Multidimensional Scale of Perceived Social Support, Survey of Perceived Organizational Support, Perceptions of Postgraduate Students’ Writing Skills, Rosenberg Self-esteem Scale, Motivated Strategies for Learning Questionnaire, The Big Five personality structure, and Ryff’s PWB Scales. The findings showed that external factors such as social support had the strongest significant impact on postgraduate students’ PWB, followed by university support. For internal factors, self-esteem had the strongest effect on postgraduate students’ PWB, followed by self-regulated learning, conscientiousness, extraversion, and openness to experience. However, gender did not have significant moderating effects on the relationship between personality traits and postgraduate students’ PWB. The findings of the research add implication and provide useful knowledge in terms of the environment, models, theoretical frameworks, and empirical findings.